Time-dependent mechanical response of buried water pipelines to cold waves under coupled multiphysics loading - Olawale Ayinde; Fei Wang; Qunfang Hu; Delu Che; Hongyan Ji; Guanfeng An (Tunnelling and Underground Space Technology, 2026)

An oil shale ash-based Fe3O4@NaY magnetic zeolite with rapid and high removal efficiency for crystal violet - Yu Duan; Qitao Liu; Qian Wang; Yuanjun Che; Hongchen Liu; Fei Li (Journal of Environmental Chemical Engineering, 2026)

Antioxidant Enzyme Activities and Metabolic Responses of the Posterior Gills of Mud Crab (Scylla paramamosain) Under Long-Term Stress in Coastal Chloride-Dominated Low-Salt Saline-Alkali Water - Ziwei Fan; Kangxiang Qin; Fei Wang; Chenxi Che; Yuntao Li; Wenjun Li; Shan Gao; Chunlin Wang; Changkao Mu; Huan Wang (Journal of Ocean University of China, 2026)

Particulate nitrate pollution control in North China Plain and Northeastern United States: A comparison of formation mechanism and its response to gaseous pollutants - Jiaqi Wang; Xiaohui Du; Liang Wen; Fei Che; Yuechong Zhang; Jian Gao (Environmental Pollution, 2026)

Valorization of fly ash into hydrophobic mesoporous SiO₂ as a highly efficient and durable antifoaming agent for wet flue gas desulfurization - Fei Wang; Xiaoyan Yan; Xiaoke Li; Jiangtao Meng; Yu Che; Jing Wang; Yuanyuan Zhang (Journal of Environmental Chemical Engineering, 2026)

The rupture process of the September 2022 Guanshan and Chishang Earthquakes: Joint inversion of seismological and geodetic data - Wei-Yu Zhang; Yu-Sheng Sun; Yopi Serhalawan; Po-Fei Chen; Ming-Che Hsieh; Wu-Lung Chang (Journal of Asian Earth Sciences, 2026)

A beveled fluorescent optical fiber biosensor based on Ni-CDs@CA/PEGDA dual film for detection of Helicobacter pylori - Zelin Gao; Lingzhu Gou; Jiantao Zhang; Baoquan Xiao; Hengbiao Zhang; Xingdong Jiang; Fei Ma; Tuanjie Che; Dekui Zhang; Liyun Ding (Chemical Engineering Journal, 2026)

Mechanisms of water-state transformations in low-temperature thermal dewatering of sludge: Synergistic control via extracellular protein α-helix conformation and water–solid interfacial affinity - Nan Tian; Yu Hua; Fei Wang; Kai Zhang; Yuanyuan Zhang; Jing Wang; Yu Che; Jiangtao Meng; Fangqin Cheng (Bioresource Technology, 2026)

LSTM-CNN-CBAM-based prediction of NOx emissions with zonal control strategies for flexible peak-load NOx reduction in CFB coal-fired units - Jing Wang; Xinwen Liao; Yu Che; Pengcheng Wang; Yuanyuan Zhang; Fei Wang; Frédéric Marias; Haojie Rong (Journal of Cleaner Production, 2026)

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

Acid-activated hexagonal boron nitride efficiently accelerates the photocatalytic decomposition of perfluoroalkyl substances: the mediation of chlorine radical - Yi-Chin Hsieh; Ming-Han Yang; Pin-Fei Chu; Chia-Hsuan Kao; Paul Westerhoff; Wen-Che Hou (Chemical Engineering Journal, 2025)

Assessing Spatiotemporal Characteristics, Health Impacts and Related Economic Losses of PM2.5, PM10 and O3 in Beijing-Tianjin-Hebei Region from 2015 to 2020 - Ran Gao; Qin Li; Yanping Zhang; Fei Che; Xiaorui Zhang; Yijie Wang; Yijun Zhang; Xite Zheng; Quanmei Li; Fengyi Huang; Chuning Luo; Wanqi Liu; et al. (Environment, Development and Sustainability, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Improving underground pipeline resilience: Prediction and interpretability analysis of urban water distribution network pipe failures during cold waves using machine learning - Qunfang Hu; Delu Che; Qiang Zhang; Jiahua Zhou; Fei Wang; Zongyuan Zhang; Zhaoyang Song (Tunnelling and Underground Space Technology, 2025)

Corrigendum to “Molecular mechanism governing RNA-binding property of mammalian TRIM71 protein” [Sci. Bull. 69(1) (2024) 72–81] - Fandi Shi; Kun Zhang; Qixuan Cheng; Shiyou Che; Shuxin Zhi; Zhenyu Yu; Fei Liu; Feifei Duan; Yangming Wang; Na Yang (Science Bulletin, 2025)

Nonlinear dynamics and vibration mechanisms in air scroll compressors: A study on orbiting and fixed scroll pair - Xiao-Liang Yang; Bin Peng; Ming-Lang Che; Jian-Fei Shi; Zhi-Xiang Liao; Yu-Bo Zhang (International Journal of Refrigeration, 2025)

SEBS-amended in-situ mixed wall material for diesel-contaminated groundwater management - Zhe-Yuan Jiang; Xian-Lei Fu; Fei Jin; Chi Che; Zhong-Yuan Li; Guojun Cai; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Mechanisms of corrosion and corrosion scale formation in water supply networks: A review - Qunfang Hu; Jiahua Zhou; Zhan Su; Shuang Nie; Fei Wang; Zongyuan Zhang; Qiang Zhang; Delu Che (Journal of Water Process Engineering, 2025)

Constructing sodium L-aspartate assisted N-doped carbon encapsulated hollow CoP spheres with enhanced electrochemical kinetics and its derived macroporous N-doped carbon foam for high-energy density hybrid supercapacitors - Xiaolin Liu; Tian Tian; Aifeng Liu; Zengcai Guo; Jingbo Mu; Xiaoliang Zhang; Xuan Yue; Xiaoyan Liu; Fei Gao; Hongwei Che (Chemical Engineering Journal, 2025)

Chitosan hydrogel incorporated with bone marrow mesenchymal stem cell-derived exosomal TIMP2 to inhibit angiogenesis in cholangiocarcinoma - Fei Song; Dan Xu; Jiayin Che; Ming Huang; Hongyang Li (Tissue and Cell, 2025)

Bridging the gap between hyperspectral imaging and crop breeding: soybean yield prediction and lodging classification with prototype contrastive learning - Guangyao Sun; Yong Zhang; Lei Wang; Longyu Zhou; Shuaipeng Fei; Shiteng Han; Shunfu Xiao; Yingpu Che; Long Yan; Yun Xu; Yinghui Li; Lijuan Qiu; et al. (Computers and Electronics in Agriculture, 2025)

High-precision U-series dating of Panxian Dadong hominin site, Guizhou Province, southwestern China - Xiaochao Che; Fei Han; Xingsheng Zhang; Bo Cao; Ping Xiao; Guanjun Shen; Jianxin Zhao (Quaternary Science Reviews, 2025)

Epidemiology of liver diseases: global disease burden and forecasted research trends - Jia Xiao; Fei Wang; Yuan Yuan; Jinhang Gao; Lu Xiao; Chao Yan; Feifei Guo; Jiajun Zhong; Zhaodi Che; Wei Li; Tian Lan; Frank Tacke; et al. (Science China Life Sciences, 2025)

Photo-motivated heterojunctions coupling built-in electric field stimulating sulfur redox kinetics for lithium-sulfur batteries - Haifeng Zhang; Fei Ma; Ting Meng; Junwei Li; Haifei Zhu; Zeyu Geng; Wenbo Zhao; Xiaohan Wang; Penghui Wu; Abdelnaby M. Elshahawy; Qianrui Gao; Quande Che (Chemical Engineering Journal, 2025)

Analyzing the effects of extreme cold waves on urban water supply network safety: A case study from 2020 to 2021 - Qunfang Hu; Delu Che; Fei Wang; Lei He (Urban Climate, 2024)

Allergenicity risk in animal-based food proteins: Source, dietary factors effect, allergen detection and processing modification methods - Yanxiang Bi; Changqi Liu; Fei Pan; Wenjun Peng; Xiaoming Fang; Huilian Che; Wenli Tian (Trends in Food Science & Technology, 2024)

Chemical regulation of lignin spatial conformation for a multifunctional soft material with a novel energy dissipation mechanism - Yingying Su; Xiao Han; Guanda Che; Jinghui Zhou; Yao Li; Sheng Cheng; Cong Wang; Xu Fei (Chemical Engineering Journal, 2024)

Decreased soil pH weakens the positive rhizosphere effect on denitrification capacity - Jun WANG; Zongxiang ZHANG; Fei LIANG; Zhao CHE; Yongkang WEN; Manyu ZHANG; Wenjun JIN; Zhaorong DONG; He SONG (Pedosphere, 2024)

Disulfidptosis: A new type of cell death - Fei Xiao; Hui-Li Li; Bei Yang; Hao Che; Fei Xu; Gang Li; Cheng-Hui Zhou; Sheng Wang (Apoptosis, 2024)
Disulfidptosis is a novel form of cell death that is distinguishable from established programmed cell death pathways such as apoptosis, pyroptosis, autophagy, ferroptosis, and oxeiptosis. This process is characterized by the rapid depletion of nicotinamide adenine dinucleotide phosphate (NADPH) in cells and high expression of solute carrier family 7 member 11 (SLC7A11) during glucose starvation, resulting in abnormal cystine accumulation, which subsequently induces andabnormal disulfide bond formation in actin cytoskeleton proteins, culminating in actin network collapse and disulfidptosis. This review aimed to summarize the underlying mechanisms, influencing factors, comparisons with traditional cell death pathways, associations with related diseases, application prospects, and future research directions related to disulfidptosis.

Metaphire guillelmi exhibited predominant capacity of arsenic efflux - Xiayun Zang; Mingyue He; Yuanzhou Xu; Ting Che; Fei Wang; Jingjing Xu; Huijuan Zhang; Feng Hu; Li Xu (Chemosphere, 2024)

Permafrost thawing caused by the China-Russia Crude oil pipeline based on multi-type data and its impacts on geomorphological reshaping and water erosion - Kai Gao; Guoyu Li; Yapeng Cao; Chunqing Li; Dun Chen; Gang Wu; Qingsong Du; Fei Wang; Fedorov Alexander; Fuqiang Che; Zhenrong Zhang; Luyao Bai; et al. (CATENA, 2024)

Evaluating the performance and influencing factors of three portable black carbon monitors for field measurement - Liqing Wu; Yicheng Shen; Fei Che; Yuzhe Zhang; Jian Gao; Chong Wang (Journal of Environmental Sciences, 2024)

Source characterization of Intermediate-Depth earthquakes in southern Java, Indonesia - M. Megawati; Kuo-Fong Ma; Po-Fei Chen; Dimas Sianipar; Ming-Che Hsieh (Journal of Asian Earth Sciences, 2024)

Common vetch intercropping with reduced irrigation ensures potato production by optimizing microbial interactions - Ting Che; Xinyue Zhang; Mingyue He; Fei Wang; Na Li; Xiayun Zang; Zhuoliang Xiao; Yuanzhou Xu; Feng Hu; Yongfeng Ren; Huijuan Zhang; Li Xu; et al. (Field Crops Research, 2024)

Enhanced microalgal biomass and lipid production with simultaneous effective removal of Cd using algae-bacteria-activated carbon consortium added with organic carbon source - Jianke Huang; Bocheng Su; Xingyi Fei; Jiayi Che; Ting Yao; Ruizeng Zhang; Sanjiong Yi (Chemosphere, 2024)

Analysis of the spatiotemporal changes in global land cover from 2001 to 2020 - Qiaoqiao Jing; Jianjun He; Yarong Li; Xianyu Yang; Yue Peng; Hong Wang; Fei Yu; Jie Wu; Sunling Gong; Huizheng Che; Xiaoye Zhang (Science of The Total Environment, 2024)

Molecular mechanism governing RNA-binding property of mammalian TRIM71 protein - Fandi Shi; Kun Zhang; Qixuan Cheng; Shiyou Che; Shuxin Zhi; Zhenyu Yu; Fei Liu; Feifei Duan; Yangming Wang; Na Yang (Science Bulletin, 2024)

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

Strong bacterial stochasticity and fast fungal turnover in Taihu Lake sediments, China - Shu-Hang Wang; Sheng-Wu Yuan; Fei-Fei Che; Xin Wan; Yi-Fei Wang; Dian-Hai Yang; Hai-Jiang Yang; Dong Zhu; Peng Chen (Environmental Research, 2023)

Propineb induced notochord deformity, craniofacial malformation, and osteoporosis in zebrafish through dysregulated reactive oxygen species generation - Wei Yuan; Ying Hu; Chen Lu; Jun Zhang; Ye Liu; Xinran Li; Kun Jia; Yong Huang; Zekun Li; Xiaomei Chen; Fei Wang; Xiaokun Yi; et al. (Aquatic Toxicology, 2023)

High-throughput calculation of organ-scale traits with reconstructed accurate 3D canopy structures using a UAV RGB camera with an advanced cross-circling oblique route - Shunfu Xiao; Yulu Ye; Shuaipeng Fei; Haochong Chen; Bingyu zhang; Qing li; Zhibo Cai; Yingpu Che; Qing Wang; AbuZar Ghafoor; Kaiyi Bi; Ke Shao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

GrpE and ComD contribute to the adherence, biofilm formation, and pathogenicity of Streptococcus suis - Fei Yu; Chunliu Dong; Yuefeng Zhang; Ruixiang Che; Chunmei Xie; Yanyan Liu; Zhiyun Zhang; Lu Li; Xueying Chen; Xuehui Cai; Gang Wang; Yanhua Li (Archives of Microbiology, 2023)

Assessment of toxic mechanisms and mode of action to three different levels of species for 14 antibiotics based on interspecies correlation, excess toxicity, and QSAR - Jin J. Li; Ya X. Yue; Jie F. Jiang; Sheng J. Shi; Hui X. Wu; Yuan H. Zhao; Fei F. Che (Chemosphere, 2023)

Design of novel double-layer coated ammonium polyphosphate and its application in flame retardant thermoplastic polyurethanes - Mei Wan; Congling Shi; Xiaodong Qian; Yueping Qin; Jingyun Jing; Honglei Che; Fei Ren; Jian Li; Bin Yu; Keqing Zhou (Chemical Engineering Journal, 2023)

Assessment of permafrost disturbances caused by two parallel buried warm-oil pipelines: A case study at a high-latitude wetland site in Northeast China - Fei Wang; Guoyu Li; Wei Ma; Dun Chen; Gang Wu; Yapeng Cao; Yanhu Mu; Yuncheng Mao; Jun Zhang; Kai Gao; Xinbin Wang; Hongyuan Jing; et al. (Cold Regions Science and Technology, 2023)

Unraveling Physiological and Metabolomic Responses Involved in Phlox subulata L. Tolerance to Drought Stress - Yan Xiong; Yanting Qu; Hui Han; Fei Chen; Li Li; Huanwei Tang; Daidi Che; Xing Zhang (Plant Molecular Biology Reporter, 2021)

Reclassification of Brevibacterium frigoritolerans DSM 8801T as Bacillus frigoritolerans comb. nov. Based on Genome Analysis - Guo-Hong Liu; Bo Liu; Jie-Ping Wang; Jian-Mei Che; Peng-Fei Li (Current Microbiology, 2020)

Research Progress on Estimation of the Atmospheric Boundary Layer Height - Hongsheng Zhang; Xiaoye Zhang; Qianhui Li; Xuhui Cai; Shaojia Fan; Yu Song; Fei Hu; Huizheng Che; Jiannong Quan; Ling Kang; Tong Zhu (Journal of Meteorological Research, 2020)

Detecting and attributing vegetation changes in Taihang Mountain, China - Shi Hu; Fei-yu Wang; Che-sheng Zhan; Ru-xin Zhao; Xiong-guo Mo; Liang-mei-zi Liu (Journal of Mountain Science, 2019)

Interferon-γ regulates cell malignant growth via the c-Abl/HDAC2 signaling pathway in mammary epithelial cells - Wen-bo Ren; Xiao-jing Xia; Jing Huang; Wen-fei Guo; Yan-yi Che; Ting-hao Huang; Lian-cheng Lei (Journal of Zhejiang University-SCIENCE B, 2019)

The mechanism of color fading in sunburned apple peel - Yulian Liu; Nianlai Chen; Cunwu Zuo; Yuxia Wu; Fei Che; Baihong Chen (Acta Physiologiae Plantarum, 2019)

Genome-wide DNA methylation analysis in jejunum of Sus scrofa with intrauterine growth restriction - Yue Hu; Liang Hu; Desheng Gong; Hanlin Lu; Yue Xuan; Ru Wang; De Wu; Daiwen Chen; Keying Zhang; Fei Gao; Lianqiang Che (Molecular Genetics and Genomics, 2018)

Aerosol optical properties and radiative impacts in the Pearl River Delta region of China during the dry season - Boru Mai; Xuejiao Deng; Zhanqing Li; Jianjun Liu; Xiang’ao Xia; Huizheng Che; Xia Liu; Fei Li; Yu Zou; Maureen Cribb (Advances in Atmospheric Sciences, 2018)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

Complex longitudinal diversification across South China and Vietnam in Stejneger's pit viper, Viridovipera stejnegeri (Schmidt, 1925) (Reptilia: Serpentes: Viperidae) - Peng Guo; Qin Liu; Fei Zhu; Guang H. Zhong; Xin Chen; Edward A. Myers; Jing Che; Liang Zhang; Thomas Ziegler; Truong Q. Nguyen; Frank T. Burbrink (Molecular Ecology, 2016)
Viridovipera stejnegeri is one of the most common pit vipers in Asia, with a wide distribution in southern China and Vietnam. We investigated historical demography and explored how the environment and climatic factors have shaped genetic diversity and the evolutionary history of this venomous snake. A total of 171 samples from 47 localities were sequenced and analysed for two mitochondrial gene fragments and three nuclear genes. Gene trees reveal the existence of two well‐supported clades (Southwest China and Southeast China) with seven distinct and strongly supported, geographically structured subclades within V. stejnegeri . Estimation of divergence time and ancestral area suggests that V. stejnegeri originated at ~6.0 Ma in the late Miocene on the Yunnan–Guizhou Plateau. The estimated date of origin and divergence of the island populations of Taiwan and Hainan closely matches the geological origin of the both islands. The mt DNA gene tree reveals the presence of west–east diversification in V. stejnegeri populations. Complex orogenesis and heterogeneous habitats, as well as climate‐mediated habitat differentiation including glacial cycles, all have influenced population structure and the distribution of this taxon. The validity of V. stejnegeri chenbihuii is questionable, and this subspecies most probably represents an invalid taxon.

Molecular phylogeography of white‐lipped tree viper ( Trimeresurus ; Viperidae) - Fei Zhu; Qin Liu; Jing Che; Liang Zhang; Xin Chen; Fang Yan; Robert Murphy; Cong Guo; Peng Guo (Zoologica Scripta, 2016)
The white‐lipped tree viper ( Trimeresurus albolabris ) is one of the most common venomous snakes with medicine importance in South East Asia. To explore the genetic diversity, population structure and evolutionary history of Trimeresurus albolabris, we collected 98 samples from 27 localities covering its entire distribution. Two mitochondrial gene fragments (cyt‐b and ND‐4) and two nuclear genes (RAG‐1 and NT‐3) were sequenced and analysed. Bayesian inference and maximum‐likelihood methods were employed to reconstruct the phylogenetic relationships among populations based on the two mitochondrial fragments, and the median‐joining networks were depicted using nuclear genes. Divergence date and ancestral area were estimated, and the population demographic history was inferred. Both phylogenetic analyses consistently uncovered that Trimeresurus albolabris was monophyletics, with five geographically structured lineages. Divergence date and ancestral area estimation indicated that T. albolabris originated in northern Thailand and eastern Myanmar at c . 7.15 Ma. Population dynamics analyses showed the southern China lineage has experienced population expansion and contraction, but the others have not. Both the interglacial expansion and the highly heterogeneous habitats resulting from the uplift of the Plateau played a joint role in shaping the present distribution and population structure. The evolutionary history of T. albolabris can be explained by a pattern of two direction dispersal: first from North to South, and then from West to East.

Double-Edged Roles of Nitric Oxide Signaling on APP Processing and Amyloid-β Production In Vitro: Preliminary Evidence from Sodium Nitroprusside - Zheng-Xu Cai; Hui-Shu Guo; Che Wang; Min Wei; Cheng Cheng; Zhao-Fei Yang; Yin-Wang Chen; Wei-Dong Le; Song Li (Neurotoxicity Research, 2016)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

Triterpenoid saponins from Ilex mamillata C.Y. Wu ex C.J. Tseng - Che Yan-Yun; Zhang Liang; Li Ning; Zeng Ke-Wu; Tu Peng-Fei (Natural Product Research, 2012)

Combination of flavopiridol and embelin effectively inhibit cell growth in hepatocellular carcinoma depending on regulatory relationship between CDK6 and XIAP - Yufang Che; David Y. Zhang; Fei Ye; Benyan Wu; Bo Jiang (Medicinal Chemistry Research, 2012)

Helicobacter pylori HP0876 is Dispensable for Heme–Iron Acquisition but Attenuates Bacterial Adherence to Gastric Epithelial Cells - Tao Liu; Yun Shi; Xiao-fei Liu; Ying Guo; Xu-hu Mao; Che Tan; Yuan Zhuang; Liu-sheng Peng; Jin-yu Zhang; Quan-ming Zou (Current Microbiology, 2012)